2013
DOI: 10.1128/jb.01449-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HilD-Regulated Genes in Salmonella enterica Serovar Typhimurium

Abstract: b Salmonella enterica serovar Typhimurium (S. Typhimurium) pathogenicity island 1 (SPI-1) encodes a type III secretion system required for invasion of host gut epithelial cells. Expression of SPI-1 virulence genes is controlled by a complex hierarchy of transcription factors encoded within and outside SPI-1. The master regulator of SPI-1, HilA, is itself regulated by three homologous transcription factors, HilD, HilC, and RtsA. HilD activates transcription of hilA and other target genes in response to environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 58 publications
8
64
0
Order By: Relevance
“…HilD, HilC, and RtsA are homologous AraC-like regulators that bind to very similar DNA sites; therefore, when these regulators are overexpressed, they are able to self-activate their own expression and to activate the expression of one another, as well as to induce the expression of most genes belonging to the HilD regulon; however, HilD is considered to be dominant, as deletion of hilD, but not of hilC or rtsA, drastically reduces the expression of the targets of HilD (23,24,(26)(27)(28)(29)(30)(61)(62)(63)(64). Our results indicate that the expression of ssrAB is not affected in a ⌬hilC (21) or ⌬rtsA mutant, but a plasmid expressing HilC can restore the expression of ssrAB in the ⌬hilD mutant (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HilD, HilC, and RtsA are homologous AraC-like regulators that bind to very similar DNA sites; therefore, when these regulators are overexpressed, they are able to self-activate their own expression and to activate the expression of one another, as well as to induce the expression of most genes belonging to the HilD regulon; however, HilD is considered to be dominant, as deletion of hilD, but not of hilC or rtsA, drastically reduces the expression of the targets of HilD (23,24,(26)(27)(28)(29)(30)(61)(62)(63)(64). Our results indicate that the expression of ssrAB is not affected in a ⌬hilC (21) or ⌬rtsA mutant, but a plasmid expressing HilC can restore the expression of ssrAB in the ⌬hilD mutant (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…HilD also directly controls the expression of the SPI-1 genes hilD, hilC, and invF, as well as other acquired and ancestral genes located outside SPI-1, such as rtsA, flhDC, siiA, lpxR, ytfK, STM14_1282, and STM14_2342 (2,(25)(26)(27)(28)(29)(30)(31). Previously, we demonstrated that HilD directly induces the expression of the ssrAB operon, which is located in SPI-2 and codes for the SsrA/B twocomponent system, the central positive regulator of SPI-2, thus establishing a transcriptional cross talk between SPI-1 and SPI-2 (21).…”
mentioning
confidence: 99%
“…HilC and RtsA are AraC-like transcriptional regulators that bind the same DNA sequence recognized by HilD; HilC is encoded within SPI-1, whereas RtsA is encoded in another island. HilD also controls the expression of many other virulence genes located outside SPI-1, including acquired and ancestral genes, directly, or indirectly through HilA, InvF or other regulators (12,(17)(18)(19)(20)(21)(22)(23)(24)(25). In agreement with its role as a master transcriptional regulator for a high number of genes, the expression, concentration and activity of HilD is tightly controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Following growth at 42°C, there was reduced expression of SPI-1 genes. Gene expression studies conducted at 42°C demonstrated reduced activation of the rtsA gene, which is directly activated by HilD (15), suggesting a reduction in the level of either HilD or HilD protein activity in response to growth at 42°C. To gain insight into the mechanism resulting in the inability to activate SPI-1 at 42°C, we utilized an inducible system to test the roles of Fur, FliZ, HilC, RtsA (STM14_5188), and HilD.…”
mentioning
confidence: 99%
“…Recently, several works have contributed to our understanding of the complex regulation of SPI-1 (12)(13)(14). In addition, the DNA binding sites of the HilD protein have been mapped and include several genes that are coregulated by HilC and RtsA (15), suggesting that reduced activation by one of the three activators may influence the activation of coregulated genes.…”
mentioning
confidence: 99%